Unpacking Students’ Metacognitive Experiences in Writing Course: The Effects of Strategy Instruction - Rika Riwayatiningsih; Dwi Rukmini; Issy Yuliasri; Hendi Pratama (Universitas Negeri Semarang, 2022)
Recently there has been a number of consideration research on metacognition. However, little attention has drawn to metacognitive experiences especially in writing enterprises. In view of this, the present study investigated students’ metacognitive experiences gathered from their writing in English as a foreign language (EFL) course. A set of semi- structured interview was used as the database to , first, explain students’ judgments and feelings related to their mental effort, confidence, satisfaction, and task difficulty before, during, and after their cognitive process in writing and, secondly, the relations of students’ metacognitive experiences and their writing performance were also assessed. To this end, 10 voluntory students who have participated in the learning of writing course have been recruited to take part on the interview. A series of questions were given to the participants related to the metacognitive experiences that comprise metacognitive knowledge and metacognitive strategies they run while learning writing. The outcomes of the study showed that students had varied problems solving strategies reflected from the different individual’s control of the cognitive regulation. The findings also indicated that there were positive outcomes in favor of the metacognitive strategies used in the writing course particularly when the strategies were correlated to the manifestation of the metacognitive knowledge. This study has practical implications on the prominent of metacognitive experiences that can be activated in writing instructions to support learning achievement.